2011
DOI: 10.1007/s10238-011-0146-5
|View full text |Cite
|
Sign up to set email alerts
|

Natural resistance to apoptosis correlates with resistance to chemotherapy in colorectal cancer cells

Abstract: Defects in apoptotic machinery vary among individual cancer cells, and the efficacy of chemotherapy in killing cancer cells depends on the successful induction of apoptosis. This study tested the hypothesis that the intrinsic ability of a cancer cell's natural resistance to apoptosis would indicate its ability in resistance to chemotherapy. Four widely studied human colorectal cancer cell lines, SW480, HT-29, LoVo and Caco-2, were examined for their apoptotic fates in spontaneous cultures for up to 6 days usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…In this study, we demonstrated the usefulness of Ad-Vpr in inhibition of colorectal cancer cell viability, further validating previous in vivo and in vitro studies on different human cancer (6)(7)(8)(9). The advantage of Ad-Vpr is that Vpr is a 96 amino acid 14-kDa protein and induces G2 cell cycle arrest and apoptosis in proliferating cells (6)(7)(8)(9). Our current study also confirmed the effects of Vpr in multidrug-resistant colorectal cancer cells.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, we demonstrated the usefulness of Ad-Vpr in inhibition of colorectal cancer cell viability, further validating previous in vivo and in vitro studies on different human cancer (6)(7)(8)(9). The advantage of Ad-Vpr is that Vpr is a 96 amino acid 14-kDa protein and induces G2 cell cycle arrest and apoptosis in proliferating cells (6)(7)(8)(9). Our current study also confirmed the effects of Vpr in multidrug-resistant colorectal cancer cells.…”
Section: Discussionsupporting
confidence: 87%
“…Gamrekelashvili et al (19) reported that necrosis may inhibit cancer recurrence by acquiring tolerance without inducing tumor immunity such as apoptosis. In our study, DHL-TauZnNa showed an antiproliferative effect associated with autophagy in HT-29 cells, which exhibit resistance to apoptosis and chemoresistance (20), suggesting that DHL-TauZnNa may be a new therapeutic strategy against cancer cells with resistance to apoptosis. In the present study, DHL-TauZnNa induced G2/M-phase cell cycle arrest.…”
Section: Discussionmentioning
confidence: 53%
“…This severity of colorectal cancer is probably due to development of metastasis and chemoresistance of colorectal cancer cells (Gallagher and Kemeny, 2010;Zhang et al, 2012). Recent data revealed promising potential for drugs initially designed for treatment of inflammation and infection in therapy of cancers whose tumorigenesis is related to the above-mentioned processes.…”
Section: Introductionmentioning
confidence: 99%